The Impact of CRM (Customer Orientation and Technology Based CRM) Implementations on Call Center Employee's Job Performance: Evidence from Malaysia Call Centers - Al Jumah, Ahmad Ibrahim (2012)
Customer Relationship Management (CRM) is a strategy used to learn more about customers' needs and behaviors in order to develop stronger relationships with them. Good customer relationships are at the heart of business success (Thomas Wailgum 2007). Nowadays, the importance of service industries growing every day through its impact on the product and the consumer From this point, while there has been some research on job performance in call centers, there is a lack of research on this particular topic particularly Malaysia call center context. The aim of the present study is to prove that a correlation exists between job satisfaction and the levels of (customer orientation and technology based CRM). The sample consisted of 105 participants from different call centers in Malaysia. Data were collected using the job performance survey which is a self-administered questionnaire (Cleo R. Jenkins & Don A. Dillman, 1995) to measure the influence of customer orientation and technology based CRM on job performance in Malaysia call center. Furthermore, the study found a relationship between CRM dimension (customer orientation and technology based CRM) and employee job performance in call center. Moreover, the research findings indicated that the two of hypothesized positive relationship between customer orientation and technology based CRM with employee job performance. Key benefits for practitioners and academics were finally discussed under the theoretical and practical implications.